A look behind the "Iron curtain". Danger from the East. Submitted to the delegates of the 2nd Congress of the International federation of free trade unions in Milan held July 4-12, 1951 ([Frankfurt-on-the-Main, 1951)
Omslag vermeldt als titel: "A glimpse behind the "Iron curtain"